Complete mapping of a novel HLA A*6801-restricted HIV-1 Tat epitope directly with a rapid modified enzyme-linked immunospot assay. - Oxenius, A; Jakobsen, B; Easterbrook, P; Boulter, J; Tun, T; Waters, A; Agudelo, J; Barnardo, M; Phillips, R; Price, D (2002)
We identified a novel HLA A*6801-restricted HIV-1 Tat-derived cytotoxic T lymphocyte (CTL) epitope using an adapted enzyme-linked immunospot assay that allows the rapid ex vivo identification of CTL epitopes together with their associated HLA Class I restriction elements. The optimal 11 amino acid residue Tat epitope efficiently stabilized the refolding of monomeric peptide-HLA A6801 complexes in vitro and fluorochrome-labelled, tetrameric peptide-HLA A6801 complexes stained CD8 T cells specific for this epitope directly ex vivo.